(R)-(−)-Xanthorrhizol Inhibits the Migration and Invasion of Triple-Negative Breast Cancer Cells by Suppressing Matrix Metalloproteinases via the NF-κB Signaling Pathway - Al-Amin, Mohammad; Fazalul Rahiman, Siti Sarah; Khairuddean, Melati; Muhamad Salhimi, Salizawati (Planta Medica, 2024)
(R)-(−)-xanthorrhizol is a bioactive sesquiterpenoid and major chemical constituent of Curcuma zanthorrhiza rhizomes. It was reported to have many pharmacological activities including nephroprotective, hepatoprotective, antimicrobial, anti-inflammatory, antioxidant, antihypertensive, antihyperglycemic, antiplatelet, estrogenic, and antiestrogenic properties. (R)-(−)-xanthorrhizol was also investigated for antiproliferative activity against many cancer cells including breast, lung, liver, ovarian, and colon cancer. It was also revealed to have a potential effect on TNBC cells MDA-MB-231. Considering the previous studies, this study has aimed to investigate the antimigratory and anti-invasive properties, as well as the possible molecular mechanisms, behind these properties. The findings of (R)-(−)-xanthorrhizol on MDA-MB-231 cell migration and invasion demonstrated significant inhibition at three different concentrations in a concentration-dependent manner, which was observed in the scratch, transwell migration, and invasion assays. Further investigation of the molecular mechanism using gelatin zymography revealed that (R)-(−)-xanthorrhizol prevented cell migration and invasion of breast cancer cells through the inhibition of matrix metalloproteinase-2 and matrix metalloproteinase-9 expression. Western blot analysis indicated that the inhibition of matrix metalloproteinases is possibly the result of the inhibition of phosphorylation in the NF-κB signaling pathway. These findings corroborate (R)-(−)-xanthorrhizol to proceed for the further studies as a possible future drug candidate for cancer patients.
Keywords: (R)-(−)-xanthorrhizol; Zingiberaceae; Curcuma zanthorrhiza, antimigratory and anti-invasive; TNBC cells MDA-MB-231; matrix metalloproteinases; NF-κB signaling pathway